2015
DOI: 10.1785/0120140107
|View full text |Cite
|
Sign up to set email alerts
|

Is Ground‐Motion Variability Distance Dependent? Insight from Finite‐Source Rupture Simulations

Abstract: The ground-motion variability sigma is a fundamental component in probabilistic seismic-hazard assessment because it controls the hazard level at very low probabilities of exceedance. So far, most of the analyses based on empirical ground-motion prediction equations do not consider any distance dependency of sigma. This study aims to analyze the potential distance dependency of ground-motion variability, especially in the near-field region, where the variability is poorly constrained due to the lack of availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 27 publications
3
4
0
Order By: Relevance
“…Our estimates of the intraevent ϕ lnPGV for R JB 11 km (ϕ lnPGV ∼ 0:6-1:0) are consistent with those of Imtiaz et al (2015) for unilateral ruptures (ϕ lnPGV ∼ 0:5-1:0). Imtiaz et al (2015) also found distance dependence of ϕ lnPGV , which they interpreted to be a consequence of the directivity effect.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Our estimates of the intraevent ϕ lnPGV for R JB 11 km (ϕ lnPGV ∼ 0:6-1:0) are consistent with those of Imtiaz et al (2015) for unilateral ruptures (ϕ lnPGV ∼ 0:5-1:0). Imtiaz et al (2015) also found distance dependence of ϕ lnPGV , which they interpreted to be a consequence of the directivity effect.…”
Section: Discussionsupporting
confidence: 82%
“…Our estimates of the intraevent ϕ lnPGV for R JB 11 km (ϕ lnPGV ∼ 0:6-1:0) are consistent with those of Imtiaz et al (2015) for unilateral ruptures (ϕ lnPGV ∼ 0:5-1:0). Imtiaz et al (2015) also found distance dependence of ϕ lnPGV , which they interpreted to be a consequence of the directivity effect. In our study, we develop a quantitative understanding of the distance decay of ϕ lnPGV from a statistical point of view (by fitting a functional form) as well as a physical point of view (by analyzing effect of rupture parameters).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Hence, the variability decreases and it is mainly controlled by the radiation pattern shape and site complexities. Similar observations have been made by Imtiaz et al (2015) and by Vyas et al (2016) though for different magnitude and distance ranges.…”
Section: Discussionsupporting
confidence: 87%
“…To examine the increase in the forecast accuracy with data assimilation time, we calculated the GMRotD50 (Boore et al, 2006), the median velocity response spectra of horizontal components for a given period in rotating the orientation of horizontal components from 0° to 90°, for the forecasted waveforms at a period of 8 s. The GMRotD50 has recently been used to assess the strength of the ground motions independent of the direction of the epicenter (e.g., Barani et al, 2015; Imtiaz et al, 2015). The GMRotD50 ratio relative to that of the expected ground motion is shown in Figure 10d, confirming that the ratio increases gradually from 15% to 60% with increasing data assimilation time from 30 to 90 s. After 100 s, the GMRotD50 ratio increased suddenly to nearly 100% as the rupture of the earthquake fault plane had been completed (section S4 for snapshots of the seismic wave propagation).…”
Section: Real‐time Forecasting Of the Lp Ground Motions For Large Nanmentioning
confidence: 99%